Dilema dan Akibat Hukum Putusan Mahkamah Konstitusi Mengenai Kewenangan Memutus Sengketa Pilkada - Iza Rumesten RS (Jurnal Konstitusi, 2014)
MK decision to hand back an arbitrary in deciding disputed local election to the MA polemical and disagreement among legal experts. There are those who argue that it was the right decision, and there are also those who argue that the MK decision is wrong. Whatever the views of different opinions, the MK has concluded that it has binding (inkracht) and inviolable. The problem now is how best to anticipate the solution of other legal issues that arise as a result of the MK decision. Thus, in this study the formulation of the issues raised is how the legal effect of the decision of  the Constitutional MK No. 1-2/PUU-XII/2014 in the general election in Indonesia. The research method of this law is normative, primary legal materials are UUD NRI of 1945, Act No. 12 of 2008 on Regional Government, Act No. 8 of 2011 on the MK. The approach used in this study is the approach to statutory interpretation and approach. From the research it can be concluded that the MK decision to restore the authority to decide election disputes to the Supreme MA is right, because the local elections are local government regime (local elections). As a result of the decision, the government should establish a local election management bodies on a par with the Commission which may be called the local election commission (KPKD) but only institution based in the provincial and district/city, for an arbitrary level  of appeal submitted to the MA.